Insulating film and laminate including the same

By using polyaryl resin and a combination of liquid crystal polyester, the problem of decreasing adhesion between liquid crystal polymer film and copper foil is solved, and the stability and high performance of FCCL are achieved.

CN119497736APending Publication Date: 2025-02-21KOLON INDUSTRIES INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380052159.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-24
Filing Date
2023-08-08
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

In the prior art, the adhesion between the liquid crystal polymer film and the copper foil is reduced, resulting in a problem of failure in adhesion during the manufacturing of FCCL.

Method used

The insulating film is produced by using a resin composition containing a polyaryl resin and two or more types of liquid crystal polyester, and the mixing ratio is adjusted to suppress an increase in viscosity of the resin composition, thereby improving the adhesion to the copper foil.

Benefits of technology

Excellent adhesion between the insulating film and the copper foil is achieved, ensuring the stability and performance of FCCL, and avoiding the problem of decreasing adhesion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005229853530000161
    Figure BDA0005229853530000161
  • Figure BDA0005229853530000171
    Figure BDA0005229853530000171
  • Figure BDA0005229853530000172
    Figure BDA0005229853530000172
Patent Text Reader

Abstract

The present application relates to an insulating film and a laminate including the same. The insulating film not only has excellent adhesive force to metal layers laminated together, but also has excellent heat resistance and film-forming performance. This insulating film can be used together with a metal layer comprising copper to manufacture a laminate such as an FCCL, and can be suitable for use in components for fifth generation mobile communications.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of Korean Patent Application No. 10-2022-0106433, filed on August 24, 2022, and Korean Patent Application No. 10-2023-0103406, filed on August 8, 2023, the disclosures of which are incorporated by reference into this specification in their entirety.

[0003] The present application relates to an insulating film and a laminate including the insulating film. Background Art

[0004] 5G refers to the fifth generation of mobile communications, which is the core infrastructure of the fourth industrial revolution. Compared with LTE (Long Term Evolution), the existing fourth generation of mobile communications, 5G mobile communications transmit large amounts of data at ultra-high speeds and connect everything in real time (ultra-low latency) (hyper-connectivity). The most important challenge of 5G mobile communication technology is to reduce transmission loss. 5G uses a high-frequency region (short wavelength region) with high linearity, but in this case, the rate at which radio waves are absorbed by the material during the wave travel (transmission loss rate) is high. Therefore, components used for 5G mobile communications such as semiconductors and PCBs (printed circuit boards) require low dielectric constant characteristics that can reduce transmission losses. In order to ensure low dielectric constant characteristics, insulators using liquid crystal polymer resins are mainly studied.

[0005] On the other hand, in addition to the above-mentioned low dielectric properties, liquid crystal polymer films have various advantages, such as high strength, high heat resistance and low hygroscopicity, but there is a problem that it is not easy to commercialize the film. This is due to the characteristics of liquid crystal polymer resins. Specifically, since liquid crystal polymer resins form a liquid crystal structure in a molten state, they have high orientation characteristics in the flow direction. Therefore, when the film is manufactured, the film is torn in the direction of discharge from the mold and has poor dimensional stability (dimensional non-uniformity), which makes it difficult to ensure film formation performance.

[0006] In order to improve the above-mentioned disadvantages of the liquid crystal polymer film, Japanese Patent No. 4091209 attempts to improve the dielectric strength of the film and the left-right vibration of bubbles (film forming ability) by applying polyarylate, which is an amorphous (or non-crystalline) polymer. In addition, Japanese Patent No. 3896324 attempts to improve dimensional stability by applying thermoplastic resins (PEI, PES, PPS and polyarylate). In this way, conventional attempts such as those in the above-mentioned patent documents focus on improving the film forming performance of the liquid crystal polymer film.

[0007] However, when the amorphous polymer or thermoplastic resin mentioned in the above patent document such as a resin containing polyarylate is applied, the adhesive force decreases due to the increase in melt viscosity. Therefore, in the process of manufacturing FCCL (flexible copper clad laminate), adhesion failure between the LCP (liquid crystal polymer) film and the copper foil may occur. Therefore, it is necessary to further improve it. Summary of the invention

[0008] Technical issues

[0009] An object of the present application is to solve the above-mentioned problems of the prior art.

[0010] Another object of the present application is to provide a liquid crystal polymer film having improved adhesion to copper foil.

[0011] All of the above objects and other objects of the present application can be solved by the present application described in detail below.

[0012] Technical Solution

[0013] According to one embodiment of the present invention, there is provided an insulating film laminated with a metal layer containing copper to form an FCCL (Flexible Copper Clad Laminate),

[0014] Among them, the surface roughness ratio calculated according to the following relationship expression satisfies 78% or more:

[0015] [Relational expression]

[0016] Surface roughness ratio (%) = (S r2 / S r1 )×100

[0017] (Wherein, in the relational expression,

[0018] S r1 is the arithmetic mean roughness of any surface of the metal layer forming the FCCL together with the insulating film, and is in the range of 0.1 μm to 0.6 μm,

[0019] S r2 is the arithmetic mean roughness of any surface of the insulating film, and is the roughness of the insulating film or the FCCL immersed in iron (III) chloride (FeCl 3 6H 2 O, anhydrous iron (III) chloride) solution and after washing, and

[0020] The arithmetic mean roughness is measured by setting 800 μm as a cutoff standard).

[0021] According to another embodiment of the present invention, there is provided a laminate comprising: (A) a metal layer comprising copper; and (B) an insulating film located on at least one surface of the metal layer, wherein the surface roughness ratio calculated according to the above relational expression satisfies 78% or more.

[0022] Now, an insulating film and a laminate including the insulating film according to an embodiment of the present disclosure will be explained in more detail.

[0023] Unless otherwise specified throughout the specification, the technical terms used herein are for reference only to specific embodiments and are not intended to limit the present disclosure.

[0024] As used herein, the singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise.

[0025] As used herein, the terms “include” or “comprising” specify specific features, regions, integers, steps, operations, elements and / or components, but do not exclude the existence or addition of different specific features, regions, integers, steps, operations, elements, components and / or groups.

[0026] The present invention can include various modifications, and can be implemented in many different forms, and specific embodiments of the present invention will now be provided and described in detail. However, it should be understood that the present invention is not limited to specific embodiments, but includes all modifications, equivalents or substitutes that do not depart from the technical concept and scope of the present invention.

[0027] According to a specific embodiment of the present application, there are provided an insulating film (or liquid crystal film) which solves the above-mentioned problems of the prior art and has improved adhesion to a copper foil, and a laminate including the insulating film.

[0028] In this regard, the inventors of the present application have confirmed that a liquid crystal polymer film manufactured by applying a polyarylate resin shows a certain degree of effect in improving the film-forming properties of the liquid crystal polymer film, but the adhesion between the liquid crystal polymer film and the copper foil is reduced. Specifically, the inventors of the present application have judged that in the conventional method for manufacturing a liquid crystal polymer film, due to the application of the polyarylate resin, the viscosity of the resin composition increases, which reduces the wettability during the bonding process with the copper foil, and sufficient adhesion is not achieved between the copper foil and the insulating film, so the above-mentioned problems occur, and the invention of the present application for solving these problems has been completed.

[0029] Therefore, according to one embodiment of the present invention, there is provided an insulating film laminated with a metal layer containing copper to form an FCCL (Flexible Copper Clad Laminate),

[0030] Among them, the surface roughness ratio calculated according to the following relationship expression satisfies 78% or more:

[0031] [Relational expression]

[0032] Surface roughness ratio (%) = (S r2 / S r1 )×100

[0033] (Wherein, in the relational expression,

[0034] S r1 is the arithmetic mean roughness of any surface of the metal layer forming the FCCL together with the insulating film, and is in the range of 0.1 μm to 0.6 μm,

[0035] S r2 is the arithmetic mean roughness of any surface of the insulating film, and is the roughness of the insulating film or the FCCL immersed in iron (III) chloride (FeCl 3 6H 2 O, anhydrous iron (III) chloride) solution and after washing, and

[0036] The arithmetic mean roughness is measured by setting 800 μm as a cutoff standard).

[0037] In a specific embodiment, the present application relates to an insulating film.

[0038] The present application uses a resin composition comprising a polyarylate resin and two or more types of liquid crystal polyesters, and adjusts the mixing ratio, so that the viscosity of the resin composition can be suppressed and the adhesion to the copper foil can be improved. In one embodiment, the two or more types of liquid crystal polyesters may include a low melting point liquid crystal polyester resin and a high melting point liquid crystal polyester resin with different melting points. Therefore, the present application can provide an insulating film for forming a flexible copper clad laminate (FCCL) having an excellent surface roughness ratio and a laminate including the insulating film.

[0039] That is, the insulating film can be laminated with a metal layer containing copper and used to form an FCCL (flexible copper clad laminate), and can have properties suitable for such applications (for example, properties that can solve the above-mentioned problems of the prior art). Specifically, the insulating film can meet the surface roughness described later and be formed of the components described later.

[0040] In a specific embodiment of the present application, the insulating film satisfies a surface roughness ratio of 78% or more, and the surface roughness ratio is calculated according to the following relational expression:

[0041] [Relational expression]

[0042] Surface roughness ratio (%) = (S r2 / S r1 )×100

[0043] Among them, in the relational expression, S r1 It can refer to the arithmetic mean roughness of any surface of the metal layer that forms the FCCL together with the insulating film. r1 Any surface of the metal layer may refer to, for example, a surface of the metal layer facing the insulating film or in contact with the insulating film when manufacturing the FCCL. Any surface of the metal layer (copper foil) laminated together with the insulating film when manufacturing the FCCL may generally have an arithmetic mean roughness (S R) of 0.1 μm or more, 0.2 μm or more, 0.3 μm or more, 0.4 μm or more, or 0.5 μm or more, and 0.6 μm or less, 0.5 μm or less, 0.4 μm or less, 0.3 μm or less, or 0.2 μm or less. r1 ).

[0044] In the relational expression, S r2 It can refer to the arithmetic mean roughness of any surface of the insulating film. In this case, measure S r2 Any surface of the insulating film may refer to, for example, a surface of the insulating film facing a metal layer (eg, copper foil) or in contact with a metal layer (eg, copper foil) when manufacturing FCCL. According to a specific embodiment of the present application, S r2 The insulating film or FCCL (formed by laminating the insulating film with the metal layer) can be immersed in iron (III) chloride (FeCl 3 6H 2 The concentration of the iron (III) chloride solution (i.e., the weight % of the iron (III) chloride excluding the solvent in 100 weight % of the solution) may be 90% or more, 95% or more, and 100% or less, although not particularly limited.

[0045] In a specific embodiment of the present disclosure, the arithmetic mean roughness as described above can be measured by setting 800 μm as a cutoff standard. And, although not particularly limited, such arithmetic mean roughness can be measured, for example, using a known device such as an optical surface roughness meter (3D profiler).

[0046] Regarding the above-mentioned problems of the prior art, for example, due to the increase in the melt viscosity of the insulating film, the adhesive force is reduced. The inventors of the present application have experimentally confirmed that when the surface roughness of the insulating film is designed to be similar to the surface roughness of the metal layer (e.g., copper foil), the degradation of the adhesive force can be prevented. Specifically, as confirmed in the following experiment, if the adhesion between the metal layer (e.g., copper foil) forming the FCCL and the insulating film is insufficient, there is a large difference between the surface roughness of the insulating film and the surface roughness of the copper foil before etching. Therefore, it is necessary to design the insulating film so that the surface roughness of the insulating film (after etching) can follow the surface roughness of the copper foil before etching to a certain extent. This design includes, for example, controlling the viscosity (melt viscosity) of the insulating film to less than 1,000 poise, as described later.

[0047] In an exemplary embodiment, the lower limit of the surface roughness ratio calculated according to the above relationship expression can be 79% or more, 80% or more, 81% or more, 82% or more, 83% or more, 84% or more, 85% or more, 86% or more, 87% or more, 88% or more, 89% or more, 90% or more, 91% or more, 92% or more, 93% or more, 94% or more, 95% or more, 96% or more, 97% or more, 98% or more, or 99% or more. And, the upper limit can be, for example, 100% or less, specifically 99% or less, 98% or less, 97% or less, 96% or less, or 95% or less.

[0048] In one exemplary embodiment, the insulating film may have a film viscosity of 1,000 poise or less. In another exemplary embodiment, the insulating film may have a film viscosity of 300 poise to 1,000 poise or less. (provided that the film viscosity is measured at 320° C. and a shear rate of 500 / sec). Such a viscosity satisfies the surface roughness ratio calculated according to the above relationship expression, and can prevent the insulating film from having a decreased adhesion to the copper foil. In addition, such a viscosity makes it possible to obtain a higher adhesion than expected in the prior art when using polyarylate as a component of the insulating film.

[0049] For example, the lower limit of the film viscosity of the insulating film may be 300 poise or more, 350 poise or more, 400 poise or more, 450 poise or more, 500 poise or more, 550 poise or more, 600 poise or more, 650 poise or more, 700 poise or more, 750 poise or more, 800 poise or more, 850 poise or more, 900 poise or more, or 950 poise or more. Also, the upper limit of the film viscosity of the insulating film may be, for example, 950 poise or less, 900 poise or less, 850 poise or less, 800 poise or less, 750 poise or less, 700 poise or less, 650 poise or less, 600 poise or less, 550 poise or less, 500 poise or less, 450 poise or less, 400 poise or less, or 350 poise or less.

[0050] The insulating film may be formed or manufactured so as to satisfy at least the above-mentioned surface roughness ratio and / or film viscosity.

[0051] In this regard, according to one embodiment of the present application, the insulating film may include polyarylate and a liquid crystal polymer resin. More specifically, the insulating film may be manufactured from a composition comprising polyarylate and a liquid crystal polymer resin. More specifically, the insulating film may be manufactured from a composition comprising polyarylate and two or more types of liquid crystal polymer resins (more preferably, two or more types of liquid crystal polyester resins with different melting points).

[0052] For example, the insulating film can be formed by melt-molding a composition containing an insulating film-forming component. Specifically, the insulating film can be obtained by melting and kneading a composition containing polyarylate and a liquid crystal polymer resin with an extruder, and discharging the molten resin through a slit in a mold. A T-shaped mold or a circular mold can be used in this process.

[0053] Alternatively, the extruded insulating film may be stretched. As a stretching method, known techniques such as uniaxial stretching, biaxial stretching, expansion or lamination stretching may be considered.

[0054] According to another exemplary embodiment, the insulating film laminate can be formed by forming an insulating film in a mold slit and simultaneously bonding different types of thermoplastic polymer films. As different types of thermoplastic polymers that can be used at this time, polyolefins such as polyethylene, polypropylene, and ethylene-α-olefin copolymers are included; or polyesters such as polystyrene, polycarbonate, polyethylene terephthalate, or polybutylene terephthalate can be used. In addition, polyacetal, polyamide, polyphenylene ether, polyether sulfone, ethylene-vinyl acetate copolymer, polyvinyl chloride, polyvinylidene chloride, polyphenylene sulfide, fluororesin, etc. can be used.

[0055] The polyarylate used to form the insulating film is an aromatic polyester produced by a polycondensation reaction of an aromatic dicarboxylic acid and an aromatic diol, and its specific structure is not particularly limited as long as it does not prevent the above-mentioned film viscosity, elastic modulus and / or relationship expressions from being satisfied. The polyarylate is advantageously used to improve the moldability or film-forming properties of the insulating film.

[0056] On the other hand, as mentioned above, the polyarylate component as an amorphous polymer can be used to improve the film forming properties of the insulating film. Polyarylate with a high viscosity level exhibits poor fluidity during the bonding process of the insulating film and the metal layer (e.g., copper foil) by thermal bonding. Therefore, the resin may not be able to fully penetrate the surface of the copper foil, which may cause the bonding force between the insulating film and the metal layer to decrease. Therefore, it is preferred to select a liquid crystal polymer resin to prevent the bonding force from decreasing due to the use of the polyarylate resin.

[0057] The liquid crystal resin or liquid crystal polymer used to form the insulating film refers to a polymer that maintains a crystalline state in a molten state and has liquid crystal properties. There is no particular limitation on the chemical composition or structure of the liquid crystal polymer as long as it does not prevent the surface viscosity ratio and / or film viscosity from satisfying the above relationship expression.

[0058] For example, the liquid crystal polymer may include one or more liquid crystal polymers such as a thermoplastic liquid crystal polyester or a thermoplastic liquid crystal polyester into which an amide bond is introduced.

[0059] Alternatively, the liquid crystal polymer may include one or more polymers in which an isocyanate-derived bond such as an imide bond, a carbonate bond, a carbodiimide bond, or an isocyanurate bond is further introduced into the aromatic polyester or the aromatic polyester amide.

[0060] In one exemplary embodiment, the thermoplastic liquid crystal polyester may be prepared from aromatic hydroxycarboxylic acid, aromatic dihydroxy, aromatic dicarboxylic acid, aromatic diamine, aromatic hydroxylamine and / or aromatic aminocarboxylic acid monomers.

[0061] The aromatic hydroxycarboxylic acid monomer may include, for example, 2-hydroxybenzoic acid, 3-hydroxybenzoic acid, 4-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, 5-hydroxy-2-naphthoic acid, 3-hydroxy-2-naphthoic acid, 4-(4-hydroxyphenyl)benzoic acid, 4-(3-hydroxyphenyl)benzoic acid, and the like, but is not limited thereto.

[0062] The aromatic dihydroxy monomer may include, for example, 1,4-dihydroxybenzene, 1,3-dihydroxybenzene, 2,6-dihydroxynaphthalene, 2,7-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-naphthalene dicarboxylic acid, 1,6-naphthalene dicarboxylic acid, 2,6-naphthalene dicarboxylic acid, 4,4′-dihydroxybiphenyl, 4,4′-dihydroxybiphenyl ether, etc., but is not limited thereto.

[0063] The aromatic dicarboxylic acid monomer may include, for example, terephthalic acid, isophthalic acid, 2,6-naphthalene dicarboxylic acid, biphenyl-4,4'-dicarboxylic acid, 4,4'-dicarboxybiphenyl ether, and the like, but is not limited thereto.

[0064] The monomer of the aromatic diamine monomer may include, for example, 1,4-diaminobenzene, 1,3-diaminobenzene, 1,5-diaminonaphthalene, 1,8-diaminonaphthalene, and the like, but is not limited thereto.

[0065] The aromatic hydroxylamine monomer may include, for example, 4-aminophenol, 3-aminophenol, 4-amino-1-naphthol, 5-amino-1-naphthol, 6-amino-2-naphthol, 4-amino-4′-hydroxybiphenyl, and the like, but is not limited thereto.

[0066] The aromatic aminocarboxylic acid monomer may include, for example, 4-aminobenzoic acid, 3-aminobenzoic acid, 6-amino-2-naphthoic acid, and the like, but is not limited thereto.

[0067] In another exemplary embodiment, alkyl, alkoxy or halogen substituents of aromatic hydroxycarboxylic acids, aromatic dihydroxys, aromatic dicarboxylic acids, aromatic diamines, aromatic hydroxylamines, aromatic and / or aminocarboxylic acid compounds, and acylated ester-forming derivatives thereof may also be used as liquid crystal polymers.

[0068] In another exemplary embodiment, a liquid crystal polymer in which an aromatic hydroxycarboxylic acid, an aromatic dihydroxy, an aromatic dicarboxylic acid, an aromatic diamine, an aromatic hydroxylamine and / or an aromatic aminocarboxylic acid compound is copolymerized with an aliphatic dihydroxy and / or an aliphatic dicarboxylic acid compound within a range that does not inhibit the liquid crystal properties of the resin in a molten state can also be used.

[0069] In a non-limiting embodiment, the thermoplastic liquid crystal polyester may be, for example, type I composed of 4-hydroxybenzoic acid, terephthalic acid and 4,4′-dihydroxybiphenyl, type II composed of 4-hydroxybenzoic acid and 6-hydroxy-2-naphthoic acid, and type III composed of 4-hydroxybenzoic acid, terephthalic acid and ethylene glycol. Specifically, commercial products currently on the market may also be included in the liquid crystal polymer, wherein products such as Sumika Super from Sumitomo Chemical and Xydar from Solvay may be used for type I, Vectra from Celanese may be used for type II, and Rodrun from Unitika Ltd. or Novacurate from Mitsubishi Engineering-Plastics may be used for type III.

[0070] In one exemplary embodiment, the insulating film may include two or more types of liquid crystal polymer resins. In this case, the liquid crystal polymer resin may include two types of liquid crystal polymer resins with different melting points. Specifically, the insulating film may include a high melting point liquid crystal polymer resin and a low melting point liquid crystal polymer resin.

[0071] Although there is no particular limitation, the melting point temperature that distinguishes whether the liquid crystal polymer resin has a low melting point or a high melting point may be 270°C, 275°C, 280°C, 285°C, 290°C, 295°C, 300°C, 305°C, 310°C, 315°C, 320°C, 325°C, 330°C, 335°C, 340°C, 345°C or 350°C.

[0072] In one non-limiting specific embodiment, the liquid crystal polymer resin may include a low melting point liquid crystal polymer resin having a melting point of 300° C. or less and a high melting point liquid crystal polymer resin having a melting point greater than 300° C. In another non-limiting embodiment, the liquid crystal polymer resin may include a low melting point liquid crystal polymer resin having a melting point of 310° C. or less and a high melting point liquid crystal polymer resin having a melting point greater than 310° C. In another non-limiting embodiment, the liquid crystal polymer resin may include a low melting point liquid crystal polymer resin having a melting point of 320° C. or less and a high melting point liquid crystal polymer resin having a melting point greater than 320° C.

[0073] In another non-limiting embodiment, the melting points of the high melting point liquid crystal polymer resin and the low melting point liquid crystal polymer resin included in the liquid crystal polymer resin may differ by 5°C or more, 10°C or more, 15°C or more, 20°C or more, 25°C or more, 30°C or more, 35°C or more, 40°C or more, 45°C or more, or 50°C or more (based on any one of 270°C, 275°C, 280°C, 285°C, 290°C, 295°C, 300°C, 305°C, 310°C, 315°C, 320°C, 325°C, 330°C, 335°C, 340°C, 345°C, and 350°C). For example, the liquid crystal polymer resin may include a low melting point resin having a melting point of 290°C or less and a high melting point resin having a melting point of 310°C or more (melting point difference is 20°C). Alternatively, the liquid crystal polymer resin may include, for example, a low melting point resin having a melting point of 280° C. or lower and a high melting point resin having a melting point of 320° C. or higher (melting point difference is 40° C.).

[0074] In the case of a low melting point liquid crystal polymer resin, the viscosity is low, which is advantageous for ensuring moldability or film forming performance, but is insufficient for ensuring heat resistance of the film. In the case of a high melting point liquid crystal polymer resin, it is insufficient for ensuring moldability or film forming performance, but is advantageous for ensuring heat resistance of the film. In order to ensure both film forming performance and heat resistance, a high melting point liquid crystal polymer resin may be preferably mixed with a low melting point liquid crystal polymer resin.

[0075] Although not particularly limited, when the insulating film includes a high melting point liquid crystal polymer resin and a low melting point liquid crystal polymer resin having different melting points as described above, an exemplary high melting point liquid crystal polymer resin may include Vectra C950 (from Celanese) or LF-31 (from ENEOS), and an exemplary low melting point liquid crystal polymer resin may include VectraA950 (from Celanese) or CX-2199 (from ENEOS).

[0076] In an exemplary embodiment, the insulating film may include 1 wt % to 15 wt % of polyarylate and 85 wt % to 99 wt % of liquid crystal polymer resin. The liquid crystal polymer film may include a low melting point liquid crystal polyester resin and a high melting point liquid crystal polyester resin. Specifically, the insulating film may include, for example, more than 2 wt %, more than 3 wt %, more than 4 wt %, more than 5 wt %, more than 6 wt %, more than 7 wt %, more than 8 wt %, more than 9 wt % or more than 10 wt % of polyarylate. Moreover, the upper limit of the content of the polyarylate resin in the insulating film may be, for example, less than 14 wt %, less than 13 wt %, less than 12 wt %, less than 11 wt %, less than 10 wt %, less than 9 wt %, less than 8 wt %, less than 7 wt %, less than 6 wt %, less than 5 wt %, less than 4 wt %, less than 3 wt % or less than 2 wt %. At this time, the weight % is a content based on 100 wt % of the total content of the resin component forming the insulating film.

[0077] In an exemplary embodiment, the insulating film may include 15% to 60% by weight of a low melting point liquid crystal polymer resin (low melting point liquid crystal polyester resin). Specifically, the insulating film may include a low melting point liquid crystal polymer resin in an amount of more than 20% by weight, more than 25% by weight, more than 30% by weight, more than 35% by weight, more than 40% by weight, more than 45% by weight, more than 50% by weight, or more than 55% by weight. In addition, the upper limit of the content of the low melting point liquid crystal polymer resin may be less than 55% by weight, less than 50% by weight, less than 45% by weight, less than 40% by weight, less than 35% by weight, less than 30% by weight, less than 25% by weight, or less than 20% by weight. At this time, the weight % is a content based on 100% by weight of the total content of the resin component forming the insulating film.

[0078] In an exemplary embodiment, the insulating film may include a high melting point liquid crystal polymer resin (high melting point polyester resin) of 15% to 80% by weight. Specifically, the insulating film may include a high melting point liquid crystal polymer resin of 20% by weight or more, 25% by weight or more, 30% by weight or more, 35% by weight or more, 40% by weight or more, 45% by weight or more, 50% by weight or more, 55% by weight or more, 60% by weight or more, 65% by weight or more, 70% by weight or more, or 75% by weight or more. In addition, the upper limit of the content of the high melting point liquid crystal polymer resin may be 75% by weight or less, 70% by weight or less, 65% by weight or less, 60% by weight or less, 55% by weight or less, 50% by weight or less, 45% by weight or less, 40% by weight or less, 35% by weight or less, 30% by weight or less, 25% by weight or less, or 20% by weight or less. At this time, the weight % is a content based on 100% by weight of the total content of the resin component forming the insulating film.

[0079] When the above content range is satisfied, the surface roughness ratio and the film viscosity according to the above relational expressions are satisfied, and thus excellent film-forming properties, heat resistance, and adhesiveness can be ensured.

[0080] The insulating film having the above structure may have excellent heat resistance. For example, the insulating film may have an elastic modulus of 150 MPa or more at 280° C. At this time, the elastic modulus refers to the elastic modulus at 280° C., which is confirmed when the temperature is increased at a rate of 5° C. / min under the conditions of a static strain of 0.15%, a dynamic strain of 0.10%, and a frequency of 1.0 Hz.

[0081] In an exemplary embodiment of the present invention, the insulating film may satisfy an elastic modulus of 150 to 600 MPa at 280° C., which is confirmed when the temperature is increased at a rate of 5° C. / min under the conditions of static strain of 0.15%, dynamic strain of 0.10% and frequency of 1.0 Hz.

[0082] Specifically, the elastic modulus as described above is related to heat resistance. Due to the nature of applications using insulating films, there may be exposure to high temperatures or heat, and therefore, a predetermined elastic modulus must be satisfied.

[0083] For example, the lower limit of the elastic modulus can be 200MPa or more, 250MPa or more, 300MPa or more, 350MPa or more, 400MPa or more, 450MPa or more, 500MPa or more, or 550MPa or more. And, the upper limit of the elastic modulus can be, for example, 600MPa or less, 550MPa or less, 500MPa or less, 450MPa or less, 400MPa or less, 350MPa or less, 300MPa or less, 250MPa or less, or 200MPa or less. In a specific embodiment of the present application, according to the above relationship expression, the insulating film can satisfy all of the surface roughness ratio, film viscosity, and elastic modulus.

[0084] In an exemplary embodiment, the insulating film may satisfy a dielectric constant (permittivity; Dk) less than 3.4. For example, the insulating film may satisfy a dielectric constant of less than 3.3, less than 3.2, less than 3.1, or less than 3.0. If the corresponding range is satisfied, it is beneficial to reduce transmission loss. The dielectric constant can be measured using the equipment described in the experiment described later.

[0085] In an exemplary embodiment, the insulating film may satisfy a dielectric loss factor (Df) of less than 0.005. For example, the insulating film may satisfy a dielectric loss factor of less than 0.004, less than 0.003, less than 0.002, or less than 0.001. If the corresponding range is satisfied, it is beneficial to reduce transmission loss. The dielectric loss factor can be measured using the equipment described in the experiment described later.

[0086] In an exemplary embodiment, the insulating film may satisfy a peeling force (or adhesive force) of 0.5 kN / m or more, which is measured when peeling off the copper foil on a sample in which a metal layer (e.g., copper foil), an insulating film, and a metal layer (e.g., copper foil) are sequentially laminated. Specifically, the peeling force of the insulating film measured using the above-mentioned sample may be 0.6 kN / m or more, 0.7 kN / m or more, 0.8 kN / m or more, or 0.9 kN / m or more. Such a peeling force or adhesive force measurement can be performed using a peeling force tester (Chem Instrument, AR-1000) to be described later.

[0087] The insulating film of the present application can be used to manufacture a flexible copper clad laminate (FCCL). For example, the FCCL can be manufactured by laminating with a metal layer containing copper. Specifically, the FCCL can be manufactured by laminating a metal layer on an insulating film and forming a circuit pattern, and etching can be performed in the circuit pattern forming process.

[0088] Regarding the manufacture of FCCL, when laminating a metal layer on an insulating film, a hot lamination process that applies heat and pressure can be applied. The surface of the insulating film is melted by the heat applied in the above process, and the molten resin moves due to fluidity. At this time, since the viscosity of the insulating film is low and the fluidity is good, it becomes more similar to the shape of the surface of the metal layer, and this can increase the contact area between the metal layer and the insulating film. This degree can be confirmed by the surface roughness ratio in the above relationship expression. The improved adhesion between the metal layer and the insulating film with similar surface shape can be confirmed by the experimental results to be described later.

[0089] For the production of FCCL, known etching solutions can be used, for example, iron (III) chloride (FeCl 3 6H 2 O, anhydrous iron (III) chloride) to form a circuit pattern on the metal layer. Although not particularly limited, the concentration of the iron (III) chloride solution used for etching (i.e., the weight % of iron (III) chloride excluding the solvent in 100 weight % of the solution) can be 90% or more, 95% or more and 100% or less.

[0090] In order to manufacture FCCL, the metal layer that can be laminated with the insulating film of the present application contains copper. The metal layer is a so-called copper foil, and can be, for example, a rolled copper foil or an electrolytic copper foil. For example, such a metal layer can contain more than 90 weight %, more than 95 weight % or more than 99 weight % of copper, and optionally, the metal layer can contain a small amount of additives, impurities, etc.

[0091] In another embodiment of the present application, a laminate including a metal layer and an insulating film is provided. The laminate may be, for example, an FCCL, or may be used to manufacture an FCCL.

[0092] The laminate includes (A) a metal layer containing copper; and (B) an insulating film located on at least one surface of the metal layer. The laminate includes the insulating film satisfying the following properties so that it can not only have excellent film forming properties, but also have excellent adhesion between the metal layer and the insulating film.

[0093] In a specific embodiment of the present application, the insulating film included in the laminate satisfies a surface roughness ratio of 78% or more, the surface roughness ratio being calculated according to the following relational expression.

[0094] [Relational expression]

[0095] Surface roughness ratio (%) = (S r2 / S r1 )×100

[0096] Among them, in the relational expression, S r1 It can refer to the arithmetic mean roughness of any surface of the metal layer that forms the FCCL together with the insulating film. r1 Any surface of the metal layer may refer to, for example, a surface of the metal layer facing the insulating film or in contact with the insulating film. Any surface of the metal layer (e.g., copper foil) laminated together with the insulating film in the process of manufacturing FCCL may generally have an arithmetic mean roughness (S R) of 0.1 μm or more, 0.2 μm or more, 0.3 μm or more, 0.4 μm or more, or 0.5 μm or more, and 0.6 μm or less, 0.5 μm or less, 0.4 μm or less, 0.3 μm or less, or 0.2 μm or less. r1 ).

[0097] In the relational expression, S r2 It can refer to the arithmetic mean roughness of any surface of the insulating film. At this time, in a laminate such as FCCL, S is measured. r2 Any surface of the insulating film may refer to a surface of the insulating film facing the metal layer (eg, copper foil) or in contact with the metal layer (eg, copper foil). r2The insulating film or FCCL (formed by laminating the insulating film with the metal layer) can be immersed in iron (III) chloride (FeCl 3 6H 2 The concentration of the iron (III) chloride solution (i.e., the weight % of the iron (III) chloride excluding the solvent in 100 weight % of the solution) may be 90% or more, 95% or more, and 100% or less, although not particularly limited.

[0098] In one exemplary embodiment, the above arithmetic mean roughness may be measured by setting 800 μm as a cutoff standard. And, although not particularly limited, such arithmetic mean roughness may be measured using a known device such as, for example, an optical surface roughness meter (3D profiler).

[0099] The explanation on the technical meaning and specific numerical values ​​of the surface roughness ratio is the same as above and thus will be omitted.

[0100] In an exemplary embodiment, the insulating film may include a liquid crystal polymer and a polyarylate, and more preferably, it may include two types of liquid crystal polymers and polyarylates having different melting points. In addition, the insulating film satisfying the above-mentioned properties may have a film viscosity of 1,000 poise or less. This viscosity satisfies the above-mentioned surface roughness ratio and can prevent the insulating film from having reduced adhesion to the copper foil. In addition, when polyarylate is used as a component of the insulating film in the prior art, a higher adhesion than expected can be obtained. The specific viscosity value of the insulating film is the same as described above.

[0101] In an exemplary embodiment, the insulating film satisfies an elastic modulus of 150 MPa or more at 280°C. At this time, the elastic modulus refers to the elastic modulus at 280°C, which is confirmed when the temperature is increased at a rate of 5°C / min under the conditions of a static strain of 0.15%, a dynamic strain of 0.10%, and a frequency of 1.0 Hz. The description of the technical meaning and specific numerical values ​​of the elastic modulus is the same as above, and will be omitted.

[0102] In one exemplary embodiment, the metal layer of the laminate may be a patterned metal layer. Specifically, the metal layer having a predetermined pattern may be formed by removing a portion of the metal layer from a laminate in which a metal layer and an insulating film are laminated.

[0103] Except for the above contents regarding the laminate of the present application, descriptions regarding the structure included in the laminate and its manufacture and the like are the same as those described above and thus will be omitted.

[0104] The use of the above-mentioned laminate is not particularly limited, but for example, the laminate is suitable for FCCL (Flexible Copper Clad Laminate) which is a component of fifth-generation mobile communications.

[0105] Beneficial Effects

[0106] According to the present application, there are provided an insulating film having not only excellent adhesion to a metal layer laminated together but also excellent heat resistance and film-forming properties, and a laminate including the same. DETAILED DESCRIPTION

[0107] Hereinafter, the functions and effects of the present invention will be described in more detail with reference to specific embodiments of the present invention. However, these embodiments are only for illustrative purposes and therefore do not limit the scope of the present invention in any way.

[0108] Manufacturing of liquid crystal film (or insulating film)

[0109] Example 1

[0110] Thermoplastic liquid crystal polyester pellets 1 (Vectra C950 from Celanese) as a high melting point liquid crystal polymer resin, liquid crystal polyester pellets 2 (Vectra A950 from Unitika Ltd.) as a low melting point liquid crystal polymer resin, and polyarylate pellets 3 (U-Polymer U-100) are mixed, and then a twin-screw extruder (extruder temperature is about 320°C) is used to prepare mixed pellets containing the above components.

[0111] The mixed pellets of Example 1 are pellets in which the respective components are mixed in predetermined contents at levels that can satisfy the film viscosity and elastic modulus of the present application, and when preparing the mixed pellets of Example 1, 79 wt % of liquid crystal polyester pellets 1 (Vectra C950), 20 wt % of liquid crystal polyester pellets 2 (Vectra A950) and 1 wt % of polyarylate pellets 3 (U-100) are used (see Table 1 below).

[0112] The mixed pellets prepared as above were placed in a single screw extruder (LE30-30 / CV, manufactured by Labtech) to produce a film with a thickness of 50 μm. At this time, the L / D of the extruder was 30 and the diameter was 30 mm. A T die was used as a die, the slit interval of the die was 0.5 mm, and the slit width was 300 mm. In addition, the temperature of the extruder was set to 380°C, and the die temperature was set to 350°C. The screw speed in the extruder was set to 65 rpm.

[0113] Example 2 to Example 12

[0114] A film having a thickness of 50 μm was produced using the same thermoplastic liquid crystal polyester pellets and polyarylate pellets as in Example 1, except that only the contents (input amounts) were changed as shown in the following Tables 1 and 2. As shown in Example 1, the mixed pellets are pellets in which the respective components are mixed at predetermined contents at levels that can satisfy the film viscosity of the present application (see the following Tables 1 to 2).

[0115] Comparative Example 1

[0116] Thermoplastic liquid crystal polyester pellets 1 (C950 from Celanese) and polyarylate pellets 3 (U-Polymer U-100) were mixed, and then mixed pellets containing the above components were prepared using a twin-screw extruder (extruder temperature of about 320° C.).

[0117] The mixed pellets of Comparative Example 1 are pellets in which the respective components are mixed at predetermined contents at levels that can satisfy the film viscosity and / or elastic modulus of the present application, and when preparing the mixed pellets of Comparative Example 1, 99 wt % of liquid crystal polyester pellets 1 (Vectra C950) and 1 wt % of polyarylate pellets 3 (U-100) were used (see Table 3 below).

[0118] The mixed pellets of Comparative Example 1 were put into a single screw extruder (LE30-30 / CV, manufactured by Labtech) to produce a film having a thickness of 50 μm. At this time, the film production conditions were the same as those described in Example 1.

[0119] Comparative Examples 2 to 5

[0120] The thermoplastic liquid crystal polyester pellets and the polyarylate pellets were adjusted to the contents (input amounts) shown in Table 3 below to prepare mixed pellets of each comparative example. As shown in Comparative Example 1, the mixed pellets are pellets in which the respective components are mixed at predetermined contents at levels that do not satisfy the film viscosity and / or elastic modulus of the present application (see Table 3 below).

[0121] Then, the mixed pellets of each comparative example were put into a single screw extruder (LE30-30 / CV, manufactured by Labtech) to produce a film having a thickness of 50 μm. At this time, the film production conditions were the same as those described in Example 1.

[0122] Evaluation of membrane performance

[0123] For the films of Examples and Comparative Examples, film viscosity, dielectric constant, dielectric loss factor, adhesive force, heat resistance, surface roughness of copper foil before etching, and surface roughness of film surface after etching were confirmed, and the results are recorded in the following Tables 1 to 3. Evaluation items and methods are as follows.

[0124] *Dielectric constant and dielectric loss factor (unitless)

[0125] The dielectric constant and dielectric loss factor of the films of Examples and Comparative Examples were measured using a microwave molecular orientation analyzer (MOA-7015, manufactured by Oji Scientific Instruments). The frequency applied during the measurement was 15 GHz.

[0126] *Film viscosity (poise)

[0127] The melt viscosity of each film of Examples and Comparative Examples was measured using a capillary rheometer (capillary viscometer) at 320° C. The capillary rheometer had a capillary of 20 mm in length and 1 mm in diameter and a piston diameter of 12 mm, and the melt viscosity was measured at a shear rate of 500 / sec.

[0128] *Surface roughness before and after etching (μm)

[0129] 1) Copper foil etching: A copper foil with a thickness of 12 μm (JXEFL-V2 from JX Metals Corporation) was prepared. Copper foil / (each example or comparative example) film / copper foil laminate was produced to evaluate adhesion. The laminate was cut into 10 mm wide x 20 mm long and then immersed in iron (III) chloride (FeCl 3 6H 2 O, anhydrous iron (III) chloride) solution (concentration of about 97%) for 30 minutes, and then washed with running water.

[0130] 2) Surface roughness of copper foil before etching and surface roughness of film surface after etching: The arithmetic mean roughness of the surface is measured using a 3D optical profiler (NPFLEX, manufactured by Bruker). Specifically, in vertical scanning interferometry (VSI) mode, the microscope magnification is set to 50x, a surface image with a size of 95 μm in length and 126 μm in width is measured, and then the arithmetic mean roughness of the surface is determined with a cutoff value of 800 μm. That is, the surface roughness of the concave and convex with a wavelength equal to or less than the cutoff value is measured. For reference, the surface roughness of the film surface after etching refers to the surface roughness of the film surface on which the copper foil is located before etching but the copper foil is removed by the etching process.

[0131] * Adhesion force (kN / m)

[0132] The liquid crystal polymer film was inserted between two copper foils using a heat press to form a laminate, and then the adhesive force was measured from the force generated when the copper foils were peeled off.

[0133] The film was cut into a size of 50 mm wide x 150 mm long, then inserted between two 12 mm copper foils (JXEFL-V2 from JX Metals Corporation) and laminated using a hot press. The pressure during hot press lamination was 20 MPa, and the hot press temperature was 300°C.

[0134] The copper foil / film / copper foil laminate prepared above was cut into 25 mm width×150 mm length to prepare a test sheet for evaluation. The peeling force generated when the copper foil was peeled using a peeling force evaluator (Chem Instrument, AR-1000) was expressed as the adhesive force.

[0135] *Elastic modulus (heat resistance) (MPa)

[0136] For the films produced in Examples and Comparative Examples, the elastic modulus (E') at 280°C was evaluated using a dynamic mechanical analyzer (DMA, DMA GABOEPLEXOR 100N, NETZSCH). The elastic modulus at 280°C was evaluated while increasing the temperature at 5°C / min under the conditions of a static strain of 0.15%, a dynamic strain of 0.10%, and a frequency of 1.0 Hz. During the evaluation, if the evaluation sample was broken and it was difficult to measure the elastic modulus, it was indicated that it was not measurable.

[0137] [Table 1]

[0138]

[0139]

[0140] [Table 2]

[0141]

[0142] [Table 3]

[0143]

[0144]

[0145] According to the results of Tables 1 to 3, it can be confirmed that Examples 1 to 12, in which two or more types of liquid crystal polymer resins with different melting points are used together, show optimal film viscosity even if they contain polyarylate resins, can suppress the increase in viscosity of the resin composition and ensure excellent coating performance, and compared with Comparative Examples 1 to 5, the adhesion to copper foil is improved.

[0146] Furthermore, in Example 1 to Example 12, the elastic modulus at 280° C. measured under the above-mentioned conditions satisfies the range of 150 MPa to 600 MPa.

[0147] On the other hand, even if one type of low melting point liquid crystal polymer or high melting point liquid crystal polymer is used, or even if the low melting point liquid crystal polymer is mixed with the high melting point liquid crystal polymer, Comparative Examples 1 to 5 do not satisfy the scope of the present application, and therefore, due to the increase in film viscosity, the adhesion to the copper foil is poor, the elastic modulus exceeds 600 MPa, or the elastic modulus cannot be measured. Therefore, the elastic modulus is related to heat resistance, and therefore, in the case of Comparative Examples 1 to 5, the heat resistance may be deteriorated.

Claims

1. An insulating film laminated with a metal layer containing copper to form an FCCL (flexible copper clad laminate), in, The surface roughness ratio calculated according to the following relational expression satisfies 78% or more: [Relational expression] Surface roughness ratio (%) = (S r2 / S r1 )×100 Among them, in the relational expression, S r1 is the arithmetic mean roughness of any surface of the metal layer forming the FCCL together with the insulating film, and is in the range of 0.1 μm to 0.6 μm, S r2 is the arithmetic mean roughness of any surface of the insulating film, and is measured after the insulating film or the FCCL is immersed in an iron (III) chloride (FeCl3·6H2O, anhydrous iron (III) chloride) solution for 1 hour and washed, and The arithmetic mean roughness is measured by setting 800 μm as a cutoff standard.

2. The insulating film according to claim 1, wherein: The insulating film has a film viscosity of 1,000 poise or less, the film viscosity being measured at 320° C. and a shear rate of 500 / sec.

3. The insulating film according to claim 1, wherein: The insulating film has a film viscosity of 300 poise to 1000 poise or less, the film viscosity being measured at 320° C. and a shear rate of 500 / sec.

4. The insulating film according to claim 1, wherein: The insulating film satisfies an elastic modulus of 150 MPa to 600 MPa at 280° C., which is confirmed when the temperature is increased at a rate of 5° C. / min under the conditions of a static strain of 0.15%, a dynamic strain of 0.10%, and a frequency of 1.0 Hz.

5. The insulating film according to claim 1, wherein: The insulating film includes a liquid crystal polymer and polyarylate.

6. A laminate comprising: (A) a metal layer comprising copper; and (B) an insulating film located on at least one surface of the metal layer, Among them, the surface roughness ratio calculated according to the following relationship expression satisfies 78% or more: [Relational expression] Surface roughness ratio (%) = (S r2 / S r1 )×100 Among them, in the relational expression, S r1 is the arithmetic mean roughness of a surface of the metal layer facing the insulating film or in contact with the insulating film, and is in the range of 0.1 μm to 0.6 μm, S r2 is the arithmetic mean roughness of one surface of the insulating film facing the metal layer or in contact with the metal layer, and is measured after the laminate is immersed in an iron (III) chloride (FeCl3·6H2O, anhydrous iron (III) chloride) solution for 1 hour and washed, and The arithmetic mean roughness is measured by setting 800 μm as a cutoff standard.

7. The laminate according to claim 6, wherein: The insulating film has a film viscosity of 1,000 poise or less, the film viscosity being measured at 320° C. and a shear rate of 500 / sec.

8. The laminate according to claim 7, wherein: The insulating film has a film viscosity of 300 poise to 1000 poise or less, the film viscosity being measured at 320° C. and a shear rate of 500 / sec.

9. The laminate according to claim 6, wherein: The insulating film satisfies an elastic modulus of 150 MPa to 600 MPa at 280° C., the elastic modulus being confirmed when the temperature is increased at a rate of 5° C. / min under the conditions of a static strain of 0.15%, a dynamic strain of 0.10%, and a frequency of 1.0 Hz.

10. The laminate according to claim 6, wherein: The insulating film includes a liquid crystal polymer and polyarylate.

Citation Information

Patent Citations

  • Apparatus for excavating bedrock

    KR1020220106433A

  • Photosensitive resin composition, display device and forming method of pattern

    KR1020230103406A